Carlos Montes Serrano. Del material de los sueños. Dibujos de arquitectura en la modernidad Valladolid: Universidad de Valladolid 2018 (diségno, 2018)
In the Preface of his latest book: Del material de los sueños. Dibujos de arquitectura en la modernidad, Carlos Montes begins by stating, “The history of architectural drawing of the last century is still to be written”. Having specified that he does not pretend to fill this void, but only to make a contribution in this sense, Montes offers us a significant insight into the drawing of architecture and of the city in the last century. There is thus a sort of return to a strict disciplinary specific, after the learned digression he indulged in his previous book Cicerón y la cultura artística del Renacimineto (2006), which analyses–within the more general theme of the diffusion of ideas and their migration in different cultural contexts–several aspects of the impact of Cicerone’s rhetorical work in the visual arts, in particular painting and architecture (read more).